Pemberdayaan Peserta Didik Mandiri dan Bermartabat dalam Pembelajaran Matematika Berbasis Double Loop Learning - Sutama, Sutama; Suyatmini, Suyatmini; Narimo, Sabar (Manajemen Pendidikan, 2020)
The performance of mathematics teachers to prepare students to be independent and dignified requires commitment from all parties. The performance of mathematics teachers promotes a culture of togetherness and family principles. The research objectives in this article are to describe 1) the conditions of learning mathematics at the research site, 2) double loop learning based mathematics learning, and 3) strategies in preparing independent and dignified students. The type and design of the research in this article is ethnographic qualitative. The research subjects were mathematics teachers, school principals, and students of SMP Negeri 1 Kartasura Sukoharjo even semester 2019/2020. The method of collecting data is observation, interview, and documentation. Data analysis techniques with flow models. The results of the study: (1) Learning mathematics in the research place tends to be directed to make students think simple. The condition of learning mathematics in the research place occurs in the paradigm of "teachers explain-learners listen". (2) Mathematics learning based on double loop learning, in the paradigm "active learners construct meaning - the teacher as a facilitator". His mindset changes reflection and action. Management model, through three stages with five provisions. (3) Preparing students to be independent and dignified, based on strong religion, core character (honesty, responsibility, discipline), lifestyle character (hard and simple work), respect for others, and exploring the potential of smart, creative, and innovative, as well as an entrepreneurial spirit.